Gibberellic Acid Concentrations and Storage of Caryocar brasiliense (Caryocaraceae) Seeds Propagated in Tubes - Lacerda, Vander Rocha [UNESP]; Pagehú, Levi Fraga; Gonçalves, Armando Pego; Vieites, Rogério Lopes [UNESP]; Lopes, Paulo Sérgio Nascimento (MDPI, 2022)
The immersion of seeds in gibberellic acid solutions can promote dormancy breaking. Storage can be dynamic in seed longevity. The objective of this work was to evaluate different concentrations of gibberellic acid applied to seeds isolated from two storage times on the emergence of C. brasiliense tree seedlings grown in tubes. There were two experiments with different planting and storage times. The seeds were extracted from the endocarp. In both, a randomized block design was used with the following seven treatments: 0, 50, 100, 500, 1000 and 2000 mg L−1 of GA3 and dry seeds without pre-soaking, with five replications of 20 seeds. The seeds were treated with fungicide and sown in tubes containing substrate. After 60 days, evaluations and transplantation were carried out. In the experiment with older pyrenes (seeds stored for seven months), there was high seed mortality (96.54%) and a small emergence rate (3.45%). On the other hand, when new pyrenes were used, the percentage of dead seeds was 32.71% and emergence was 62.28%. GA3 did not stimulate germination or the diameter of C. brasiliense tree seedlings, except for stem length. The 2000 concentration provided a greater stem length and greater leaf area compared to dry seeds.
Keywords: Caryocar brasilienseCambess; dormancy; germination; pequi; pequizeiro; plant hormone